Pharmacogenetics applied to smoking cessation (Research, Society and Development, 2021)
Many studies seek the basis of pharmacogenetics to elucidate nicotine addiction. Smoking has been associated with several genetic polymorphisms. This integrative review gathers information from the updated literature to assess the relationship between difficulty in smoking cessation and genetic alterations. Searches were made in the databases: PubMed, SciELO, LILACS and Academic Google. Studies indicate that even with intensive efforts to control smoking behavior, definitive smoking cessation usually only occurs after several attempts and the number of relapses is very high. Genetic factors contribute to the difficulty and success of smoking cessation efforts. However, the challenge is still to understand, in molecular terms, how genetic variations confer susceptibility to smoking cessation. In the future, more robust clinical trials will be able to individualize the type, dosage, and duration of treatment for tobacco dependence, according to the genotype of each smoker, maximizing the effectiveness of the proposed regimen. Thus, identifying the risk variants in each candidate gene, the genetic polymorphisms capable of determining how each variant alters the function of encoded proteins, are of fundamental importance to really prove this relationship between pharmacogenetics and smoking.